Analysis of Patients’ Satisfaction With the Work of Family Medicine Teams at the Primary Healthcare Center in Banja Luka - Milojević, Dragan; Stanetić, Kosana; Savić, Suzana; Petrović, Verica (General Practice, 2024)
Introduction: The primary healthcare reform in Bosniaand Herzegovina began in 1999. The focus was on theintroduction of family medicine, in comparison to the existingdispensary model of care based on the practice of generalmedicine. The reform is an ongoing process, and all changesare being implemented to improve patients’ satisfaction. Ourobjective is to analyze patients’ satisfaction and the impact ofsocio-demographic factors on patients’ satisfaction with thework of family medicine teams.Methods: This research is an observational anddescriptive study conducted in family medicine clinicsof the Primary Healthcare Centre in Banja Lukafrom February 1st to April 1st 2022.The data was gathered using the EUROPEP questionnairewhich is a standardized instrument for the evaluationof patients’ satisfaction with primary healthcare, as well asa questionnaire with socio-demographic information. Thestudy comprised 250 patients from family medicine clinicsin the city, suburbs, and countryside.Results: The analysis of 250 questionnaires has providedanswers to 23 questions in the EUROPEP instrumentassessing four domains: doctor-patient relation X̅ (4.22) SD(0.85); medical care X̅ (4.32) SD (0.90); information andsupport X̅ (4.04) SD (0.94); and organization of services X̅(3.81) SD (0.98). Socio-demographic and other patient characteristicsgreatly impact family medicine patients’ satisfactionwith healthcare services.Conclusions: In general, the patients are satisfied withthe care provided by the family medicine teams of the PrimaryHealthcare Centre in Banja Luka, and least satisfied withthe organization of services. According to individual questionsin the EUROPEP questionnaire, the patients are mostunsatisfied with reaching their doctors by phone, receivingadvice from them, spending a lot of time waiting in the waitingrooms, and scheduling their appointments.
Keywords: family medicine, patients satisfaction, EUROPEP-questionnaire